Application for Promotion of Micro, Small and Medium Enterprise Activities in Increasing Student Business Creativity Using Digital Technology - Daeli, Cosmas Samuel; Karo-Karo, Siddik; Nengsih, Yeyi Gusla (Devitara Innovations, 2024)
This research aims to develop a digital technology-based promotion application aimed at improving students' ability to promote MSME products. This application is expected to provide innovative solutions in increasing the visibility and sales of MSMEs managed by students, by providing features that support promotional activities effectively. The data collection method is carried out through field research, interviews, and direct observation. The results of the study show that this application has great potential in supporting promotional efforts and improving students' digital skills, which in turn can have a positive impact on the local and national economy.